2019
DOI: 10.3390/healthcare7020072
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Male Caregivers’ Emotional, Financial, and Physical Burden in the United States

Abstract: Men caregivers face caregiving burden, have weak support networks and are less likely to seek out programs which increase their caregiving capabilities and help them cope with this burden. Using the 2011 and 2015 National Study of Caregiving (NSOC) database and hierarchical regressions, we studied the emotional, financial, and physical burden of male caregivers as spouses, sons, and other caregivers by assessing the impact of caregiver characteristics, tasks and resources for each subgroup. We highlighted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 80 publications
(118 reference statements)
1
41
1
7
Order By: Relevance
“…Thus, this may motivate female caregivers to learn more about the condition, possibly explaining the gender difference with regards to knowledge. Alternatively, this may be linked to how male caregivers have weaker support networks and are also less likely to seek out programs that can bolster their caregiving capabilities (Lopez-Anuarbe & Kohli, 2019). In which case, their knowledge may be implicated insomuch that even if they encounter any issues with caregiving or experience any knowledge gaps in caregiving, they have less revenues to seek help, ask questions or attain appropriate advice from.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this may motivate female caregivers to learn more about the condition, possibly explaining the gender difference with regards to knowledge. Alternatively, this may be linked to how male caregivers have weaker support networks and are also less likely to seek out programs that can bolster their caregiving capabilities (Lopez-Anuarbe & Kohli, 2019). In which case, their knowledge may be implicated insomuch that even if they encounter any issues with caregiving or experience any knowledge gaps in caregiving, they have less revenues to seek help, ask questions or attain appropriate advice from.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, health care professionals have a role to play when there may be discrepancies between the care needs expressed by the patient and the care needs identified by the informal caregiver (Nakken et al, 2015). There is growing recognition that caring for a person living with a chronic condition disrupts life and can be detrimental to the physical, social and emotional health of informal caregivers and that meeting their needs is important because it ultimately impacts on the care the patient returning home experiences (Souliotis et al, 2017; Noonan et al, 2018; Lopez‐Anuarbe & Kohli, 2019). For example, work by Ek et al (2011) found how disruptive home care can be for people with advanced COPD and that support from health professionals was important in caregivers adapting to the new and additional demands placed upon them.…”
Section: Introductionmentioning
confidence: 99%
“…Older age and female gender were significantly associated with more time spent on care. Much of the literature confirms that females participate more in informal care, and spend significantly more time on caregiving for older people living with dementia compared to men [ 68 , 69 ], but much of the caregiving literature is criticized for reflecting the female perspective [ 68 , 70 , 71 ], which may marginalize, and underestimate male caregiving [ 72 ].…”
Section: Discussionmentioning
confidence: 99%